Formulating specialised Legislation to address the Growing Spectre of Cybercrime: A Comparative Study - F Cassim (Potchefstroom Electronic Law Journal, 2009)
The article looks at cyber legislation formulated to address cybercrime in the United States of America, the United Kingdom, Australia, India, the Gulf States and South Africa. The study reveals that the inability of national laws to address the challenges posed by cybercrime has led to the introduction of specialised cyber legislation. It is advocated that countries should amend their procedural laws to include intangible evidence of cybercrime, as opposed to tangible evidence of traditional crimes. It is possible that new forms of cybercrime will often emerge with evolving technology; therefore new cyber laws should be introduced to respond to these rapid changes. There should also be continuous research and training of IT security personnel, financial services sector personnel, police officers, prosecutors and the judiciary to keep them abreast of the evolving technology. International co-operation between countries is also required to address the global nature of cybercrime. To this end countries such as South Africa should ratify the Council of Europe’s Convention on Cybercrime (COECC) to serve as a deterrent against international cybercrime. A balanced approach that considers the protection of fundamental human rights and the need for the effective prosecution of cybercrime has been mooted as the way forward.